Cultural values and plagiarism: a study of Australian, Malaysian and Mauritian business students - Egan, Victor (Taiwan Institute of Business Administration, 2008)
This paper presents the results of a study which sought to distinguish attitudinal differences to the issue of plagiarism among Malaysian (n=105), Mauritian (n=49) and Australian (n=96) undergraduate business students. The results show that national culture and gender influence attitudes to plagiarism. The Malaysian students generally reported greater propensity to plagiarise because their peers were perceived to be doing so, and because of their excessive academic workload. In additon, Malaysian males reported a greater propensity to plagiarise than Malaysian females, and offshore Malaysian students were more tempted to plagiarise than their onshore counterparts. The Mauritian students reported greater propensity to plagiarise because of excessive academic workload, but were less affiliated to perceived peer action than was the Malaysian sample group. Implications for universities are provided.